Plan de negocios para la creación de un Complejo Recreacional en la comunidad de Carabuela, ciudad de Otavalo, Provincia de Imbabura. - Santacruz M. Lisbeth Alexandra -, Tituaña P. Jessica Maricela (2015)
This project was undertaken in order to benefit from the opportunity that the National Financial Corporation provides enterprises, through its program of productive and financial support. It is for this reason that we have considered the realization of a Business Plan and Investment, allowing access to this loan and which in turn serve as a proper guide for the creation of a recreational center in the community of Carabuela city Otavalo. Lack of Recreational Centers in the city of Otavalo and places that enable the development of recreational, sports and leisure, propel ventures of this nature that are attractive to both investors and for credit institutions which allocates ..